THE EFFECTS OF TEACHING METHOD AND LEARNING MOTIVATION TOWARDS STUDENT’S READING SKILLS - Zumrotul Muniroh (Deiksis, 2014)
The purpose of this study was to obtain empirical data and analyze the effect of the teaching methods and the motivation to learn through the reading skills of students overall population of class X SMA and SMA Kharismawita Mother bladder. Total sample of 30 students, or 20-25% of the population. The samples were divided into 2 groups, the first group of 30 students taught using Contextual Teaching and Learning Motivation and 30 students taught by conventional methods. This research was conducted with descriptive statistics, test Liliefors as normality test, Barlett as the homogeneity test, and ANOVAdua direction as hypothesis testing. The collection of data to test reading skills through field tests and as many as 20 multiple-choice questions, and tests for learning motivation through a questionnaire of 20 items was given to class X SMA and SMA Kharismawita Mother Bladder South Jakarta. The results of this study there was no significant interactive effect between teaching methods and motivation to learn through the reading skills of students (0755> 0:05).Keywords: reading skills, Methods of Teaching, Learning Motivation